The Effect of PISA-Based Educational Program on Mathematical Achievement - Tashtoush, Mohammad; Qasimi, Aida; Sheerawi, Nawal; AL-Shannaq, Mamoon (Acta Paedagogica Vilnensia, 2024)
This study aimed to investigate the impact of an educational program rooted in the Program for International Student Assessment (PISA) on the mathematical achievement of tenth-grade female students. The study adopted a quasi-experimental approach, with two distinct groups: an experimental group exposed to the PISA-based educational program and a control group receiving conventional instruction. A meticulously crafted mathematical achievement test served as the primary assessment tool. The findings unequivocally revealed a substantial improvement in the mathematical achievement of both study groups post-test. Notably, significant differences in arithmetic means and standard deviations were observed between the groups, with the experimental group exhibiting markedly higher achievement scores. To determine the statistical significance of these differences, ANCOVA analysis was employed, alongside effect size calculations. In addition, the displayed results indicated statistically significant differences favoring the experimental group. In conclusion, this study underscores the substantial positive impact of the educational program based on the International Study for Student Assessment PISA on the mathematical achievement of tenth-grade female students. These results contribute to the body of knowledge on effective educational strategies and emphasize the potential benefits of integrating PISA-based educational programs into math instruction.
Keywords: Educational program; PISA; Mathematical achievement; Tenth-grade students; Assessment